Tanggung Jawab Bank Syariah Indonesia Lhokseumawe dalam Melindungi Data Nasabah - Arina Nurfaza (Syntax Corporation, 2022)
Protection of customer data security so far, in addition to being regulated by regulations, is also applied by the Bank, but only the scope of conventional banks, even though there are banks that have a sharia system, but since Bank Syariah Indonesia (BSI) was officially established on February 1, 2021, it will be very interesting as a newly formed financial institution consisting of BRI Syariah, BNI Syariah and Bank Syariah Mandiri to examine the role and function of Bank Syariah Indonesia Lhokseumawe in protecting customer data. This study aims to find out how BSI Lhokseumawe's responsibility is in protecting customer data. This research is a mixed methode research (MMR), where in this study the steps taken are to combine qualitative and quantitative research approaches. The results of this study state that the responsibility of Bank Syariah Indonesia in maintaining customer data has been carried out in a structured and appropriate mechanism, in addition to the guidance of existing laws and regulations, both Banking Law, BI Regulations, and OJK regulations, in addition to customer views on data protection, from the results of qualitative and quantitative research, data obtained that customers have a positive view of the bank's efforts Sharia Indonesia in protecting its customers' data.